Growth of large-size KDP single crystals with high laser damage threshold - Pritula, I.M.; Kolybayeva, M.I.; Salo, V.I.; Puzikov, V.M.; Belikov, K.N. (Functional Materials, 2005)
It is shown that the developed method of solvent re-circulation which provides the obtaining of the crystals under optimum growth conditions at a constant temperature (Тcᵣ = 80 ℃, Vgᵣₒwₜₕ ≈ (0,8 / 1,6) * 10⁻⁶ cm/s, рН = 4) allows to grow KDP crystals with a cross-section up to 300 х 300 mm² and a bulk laser damage threshold of ≈ 60 J/cm². Показано, що розроблений метод рециркуляцiї розчинника забезпечує рiст кристалiв при постiйнiй температурi i оптимальних умовах кристалiзацiї (Ткᵣ = 80 ℃, Vкᵣ ≈ (0,8 / 1,6) * 10⁻⁶ cm/s, рН = 4), дозволяеє одержувати монокристали KDP перерiзом до 300 х 300 мм² з величиною об'емної променевої мiцностi ≈60 Дж/см². Показано, что разработанный метод рециркуляции растворителя, обеспечивающий рост кристаллов при постоянной температуре и оптимальных условиях кристаллизации (Ткᵣ = 80 ℃, Vкᵣ ≈ (0,8 / 1,6) * 10⁻⁶ cm/s, рН = 4), позволяет получать монокристаллы KDP сечением до 300 х 300 мм² с величиной объемной лучевой прочности ≈ 60 Дж/см².